The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.soilbio.2020.108102
|View full text |Cite
|
Sign up to set email alerts
|

Soil fungal diversity and functionality are driven by plant species used in phytoremediation

Abstract: Soil biodiversity loss due to pollution may affect ecosystem services negatively. This environmental problem may be solved by phytoremediation, which is an effective strategy to manage and remediate contaminated areas. During this remediation process, the establishment of plant communities may improve soil fungal community structure and, in particular, may favour mycorrhizal symbiotic associations. As a consequence, afforestation of degraded lands will have different outcomes on fungal diversity and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 103 publications
(120 reference statements)
1
8
0
2
Order By: Relevance
“…ADI can improve the composition of soil aggregates and soil aeration, while surface drip irrigation is prone to causing relative soil compaction in the tomato root zone (Lehmann et al, 2017) and better promotes the growth of Mucoromycota. Basidiomycota can produce a large number of hydrophobic hyphae (Lehmann et al, 2020) and participate in the construction of plant ectomycorrhizae (Gil‐Martínez et al, 2021); the relatively high number of root forks of A70 is likely closely related to the significant increase in the relative abundance of Basidiomycota in this treatment. This relationship is similar to the results of Milan et al (2015), except that we achieved it by conditioning the soil in a greenhouse.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…ADI can improve the composition of soil aggregates and soil aeration, while surface drip irrigation is prone to causing relative soil compaction in the tomato root zone (Lehmann et al, 2017) and better promotes the growth of Mucoromycota. Basidiomycota can produce a large number of hydrophobic hyphae (Lehmann et al, 2020) and participate in the construction of plant ectomycorrhizae (Gil‐Martínez et al, 2021); the relatively high number of root forks of A70 is likely closely related to the significant increase in the relative abundance of Basidiomycota in this treatment. This relationship is similar to the results of Milan et al (2015), except that we achieved it by conditioning the soil in a greenhouse.…”
Section: Discussionmentioning
confidence: 97%
“…A70 produced the least soil drought stress on the root system, which was conducive to the division of root cells (Zia et al, 2021). Therefore, A70 resulted in a higher number of root forks than CK, which provided more sites for interactions with ectomycorrhizae, promoted the growth of Basidiomycota (Gil‐Martínez et al, 2021), and reduced the complexity of trophic modes involving Basidiomycota (Table S1.). Previous studies have shown that soil moisture status alters root structure, thereby altering fungal community shifts associated with changes in root traits (Deveautour et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some unidentified orders of Ascomycota were detected in high abundance in soils where alfalfa and mycorrhizal poplars were present. Some studies have recognized the key role of the phylum Ascomycota in environments contaminated with organics (Aranda, 2016) and metals (Gil-Martínez et al, 2021). However, the role of Ascomycota in the transformation of soil contaminants remains poorly understood.…”
Section: Soil Microbial Propertiesmentioning
confidence: 99%
“…Different plant varieties therefore may lead to variation in fungal community characteristics. For example, differences were observed in the diversity, composition and symbiotic network of soil fungal communities among different varieties of Zea mays in China ( Kong et al, 2020 ; Gil-Martínez et al, 2021 ). However, Li et al (2018) found that rice variety did not significantly affect fungal abundance or community composition.…”
Section: Introductionmentioning
confidence: 99%